Adverse Effect of Aerosol Pesticide on Lung Dysfunction amongPaddy Farmers in Purworejo, Central Java, Indonesia - Nurcandra, Fajaria; Mahkota, Renti; Miko Wahyono, Tri Yunis (Kesmas, 2020)
The World Health Organization estimated that chronic obstructive pulmonary disease (COPD) will be the highest non-communicable disease worldwide by2030, and pesticide exposure is one of major risk factors. This study aimed to determine effect of pesticide exposure on lung dysfunction among paddyfarmers. A case-control study was performed on April - May 2016 in Purworejo. The case group comprised 66 farmers suffering from lung dysfunction during2015 based on medical records, while the control group comprised 59 neighboring farmers showing normal lung function. Both case and control groups weretested using a spirometer and COPD assessment test (CAT) questionnaire. Logistic regression analysis of pesticide quantity (OR = 0.75; 95% CI = 0.317 -1.754) and duration of spraying (OR = 1.11; 95% CI = 0.430 - 2.891) adjusted for confounders showed no clear associations. Pesticide remained a potentialhealth risk for lung dysfunction due to farming duration (OR = 5.61; 95% CI = 1.124 - 27.990) adjusted by age, personal protective equipment, records of lungdisease, smoking habit, dust exposure, and indoor air pollution. The farming duration was revealed to be a risk factor, but no clear association was found between quantity and duration of spraying to lung dysfunction.